Transthyretin Aggregation Pathway toward the Formation of Distinct Cytotoxic Oligomers - Dasari, Anvesh K. R.; Hughes, Robert M.; Wi, Sungsool; Hung, Ivan; Gan, Zhehong; Kelly, Jeffrey W.; Lim, Kwang Hun (My University, 2019)
Characterization of small oligomers formed at an early stage of amyloid formation is critical to understanding molecular mechanism of pathogenic aggregation process. Here we identifed and characterized cytotoxic oligomeric intermediates populated during transthyretin (TTR) aggregation process. Under the amyloid-forming conditions, TTR initially forms a dimer through interactions between outer strands. The dimers are then associated to form a hexamer with a spherical shape, which serves as a building block to self-assemble into cytotoxic oligomers. Notably, wild-type (WT) TTR tends to form linear oligomers, while aTTR variant(G53A) prefers forming annular oligomers with pore-like structures. Structural analyses of the amyloidogenic intermediates using circular dichroism (CD) and solid-state NMR revealthatthe dimer and oligomers have a signifcant degree of native-like β-sheet structures (35–38%), but with more disordered regions (~60%)than those of nativeTTR.TheTTR variant oligomers are also less structured than WT oligomers. The partially folded nature of the oligomeric intermediates might be a common structural property of cytotoxic oligomers.The higher fexibility of the dimer and oligomers may also compensate for the entropic loss due to the oligomerization of the monomers.